Chaturmukha linga in the mandapa - Temples of India Project Team (Jio Institute, 2024)
A Chaturmukha linga is placed on top of the stone platform in the mandapa. As per the literal meaning of the term Chaturmukha, the linga has four faces, each facing a cardinal direction. The linga is made of a black stone and is worshipped as the primary deity by the locals. According to popular lore, the Chaturmukha linga represents Shiva, Parvati, Brahma, and Vishnu. The mukha facing the east (entrance gate) is of Shiva with a heavy jatabhara on the head. The south face of the linga has a heavy jatamukuta (matted crown) on its head and hairlocks cascading down to the shoulders. The west face (rear) also has a jatamukuta, albeit carved slightly differently from the other three. The north face has snail-shaped curls culminating in a jatamukuta. The deity is adorned with a beautiful necklace. The sringara (attributes) of all the four faces of the Chaturmukha linga are done differently. This could be a representation of Maheshmurti or the trinity, with Surya also depicted.